Clinical features and management of Luc's abscess: Case report and systematic review of the literature. Issue 2 (April 2020) - Fernandez, Ignacio Javier; Crocetta, Francesco Maria; Pelligra, Irene; Burgio, Luca; Demattè, Marco
Abstract: Objectives: Luc's abscess is a rare complication of acute otitis media, with a challenging diagnosis and a controversial surgical treatment. The aim of the present study was to review the published literature in order to clarify the clinical features and the surgical management of those patients. Methods: A systematic review of the literature was carried out for published reports or case series in English language, describing a temporo-zygomatic (or Luc's) abscess which complicated an acute or chronic otitis media and/or mastoiditis, confirmed through CT scan or MRI of the petrous bone. The collected clinical and radiological data were merged and critically appraised. Results: Eighteen reports of Luc's abscess were included. Adding our case report, a total of 21 cases were included in the analysis. Abscess drainage plus myringotomy alone vs. abscess drainage plus myringotomy and mastoidectomy were the two surgical management approaches described in the literature. Patients undergoing first line mastoidectomy were successfully treated in all cases, while among those undergoing a more conservative approach, one failure required subsequent mastoidectomy. Conclusions: The clinical features of Luc's abscess are rather constant and help in rising the suspicion before the radiological diagnosis. Although cases with associated intra-cranic complications have been reported, the limited existing data do not permit to advocate the mastoidectomy over a more conservative surgical approach. However, the decision to avoid mastoidectomy as the first line surgical treatment should be based on the clinical and radiologic assessment, after an accurate counseling, particularly in the case of a pediatric patient.